2019
DOI: 10.1002/jts.22427
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Intent to Complete and Intent to Attend Intervention to Predict and Prevent Posttraumatic Stress Disorder Treatment Drop Out Among Soldiers

Abstract: Active duty military service members have high dropout rates for trauma-focused treatment in both clinical practice and research settings. Measuring patients' intent to complete (ITC) and intent to attend (ITA) treatment have been suggested as methods to reduce dropout, but no studies have examined the effectiveness of such measures. In an attempt to reduce high dropout rates, measures of ITC and ITA were included in a randomized controlled trial evaluating prolonged exposure (PE) and virtual reality exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Training and incentivizing PE/CPT therapists to develop strong treatment-specific rapport and increase the patient-centeredness with which treatment is delivered may be an effective target for engagement interventions. In an uncontrolled study, assessing patients’ intent to attend the following trauma-focused session, with a low score triggering a problem-solving discussion with the patient’s therapist, reduced treatment dropout ( Shulman et al, 2019 ); the study’s authors hypothesized the intervention’s effect was due to increased adaptation. Our results also suggest that engaging the full mental health treatment team (e.g., psychiatrists, case managers) in the goal of PE/CPT completion, perhaps through planned outreach or brief contacts after early treatment sessions, could reduce dropout rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training and incentivizing PE/CPT therapists to develop strong treatment-specific rapport and increase the patient-centeredness with which treatment is delivered may be an effective target for engagement interventions. In an uncontrolled study, assessing patients’ intent to attend the following trauma-focused session, with a low score triggering a problem-solving discussion with the patient’s therapist, reduced treatment dropout ( Shulman et al, 2019 ); the study’s authors hypothesized the intervention’s effect was due to increased adaptation. Our results also suggest that engaging the full mental health treatment team (e.g., psychiatrists, case managers) in the goal of PE/CPT completion, perhaps through planned outreach or brief contacts after early treatment sessions, could reduce dropout rates.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative methods are particularly useful for theory refinement and hypothesis generation that can guide successful intervention development ( Sofaer, 1999 ). Further, they can clarify complex patterns, like those that exist in the bidirectional therapeutic relationship in the context of fluctuating thoughts and behaviors related to treatment discontinuation ( Shulman et al, 2019 ; Sofaer, 1999 ). Qualitative work examining PTSD treatment initiation more broadly has found that treatment initiators and non-initiators experienced similar barriers to treatment, but completers had additional facilitators to help overcome those difficulties ( Sayer et al, 2009 ).…”
mentioning
confidence: 99%
“…Clinicians might partner with patients to manage treatmentrelated distress and jointly explore risk of negative consequences of treatment, as well as possible benefits of treatment despite a potential temporary increase in difficulty, in order to reframe potentially exaggerated expectancies and to prevent negative outcomes from occurring. Clinicians are often unaware of the types of concerns that may contribute to poor outcomes (Meis et al, 2023), so asking patients about their concerns throughout treatment can provide the opportunity to intervene more effectively, whether through problemsolving (Shulman et al, 2019) or another adjunctive procedure, or through bolstering PE or CPT elements (e.g., challenging treatmentinterfering stuck points, empowering patients to engage in exposure) to retain patients in care. Kehle-Forbes et al (2022) reported findings from this sample related to interpretations of ongoing or worsening symptoms as well as concerns about the impact of treatment on functioning.…”
Section: Discussionmentioning
confidence: 99%
“…As such, clinicians may be able to address thoughts of dropout through assessing Veterans’ perceptions of their symptom change continually throughout treatment and any urges to dropout from treatment. Relatedly, a recent pilot study demonstrated that simply asking patients if they intended to continue to attend therapy each session reduced treatment dropout rates, suggesting that initiative conversations about these topics holds promise for improving engagement (Shulman et al, 2019). Future studies should further explore symptom exacerbation and factors that may mitigate it, such as a strong therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%